2020
DOI: 10.1007/s13744-020-00812-8
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens Detection in the Small Hive Beetle (Aethina tumida (Coleoptera: Nitidulidae))

Abstract: Aethina tumida Murray is currently a worldwide emergent pest of Apis mellifera L. hives. Although the damaging effect on the colony stores and brood is well known, the possible role of these beetles as a disease carrier is not clear. This is the first report of DNA presence of the trypanosome honeybee parasite Lotmaria passim and Crithidia bombi, and the Apis mellifera filamentous virus (AmFV) in A. tumida. Further studies will be needed to determine if A. tumida is indeed a mechanical or biological vector of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…The prevalence of L. passim-positive individuals detected in this study (40% of all samples) mirrors that reported in a previous survey in which C. bombi was also reported in larval SHBs [22]. Additionally, we report for the first time SHB samples positive for C. mellificae.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The prevalence of L. passim-positive individuals detected in this study (40% of all samples) mirrors that reported in a previous survey in which C. bombi was also reported in larval SHBs [22]. Additionally, we report for the first time SHB samples positive for C. mellificae.…”
Section: Discussionsupporting
confidence: 89%
“…To date, only a few instances of individual SHBs bearing bee pathogens have been reported. This is the case for samples from Mexico (positive for L. passim, Apis mellifera filamentous virus (AmFV), C. bombi, Ascosphera apis, and Nosema ceranae [22]), Florida (positive for N. ceranae [20]), and other areas of the USA (positive for DWV, SBV and P. larvae [19,20,22,24]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 163 ]. Besides, it was detected in the small hive beetle as well as in A. tumida [ 148 , 164 ]. Finally, the microsporidium was found in the regurgitated pellets of the European bee-eater Merops apiaster [ 165 ].…”
Section: Discussionmentioning
confidence: 99%